Experimental investigation into gas production from methane hydrate in sediment by depressurization in a novel pilot-scale hydrate simulator - Li, Xiao-Sen; Yang, Bo; Zhang, Yu; Li, Gang; Duan, Li-Ping; Wang, Yi; Chen, Zhao-Yang; Huang, Ning-Sheng; Wu, Hui-Jie (Applied Energy, 2012)
The gas production behavior from methane hydrate in the sediment by depressurization was investigated in a novel pilot-scale hydrate simulator (PHS), a three-dimensional pressure vessel of 117.8 L Experimental results are compared with those in a cubic hydrate simulator (CHS) with the effective volume of 5.8 L to reveal the dependence of the production behavior on the size of the hydrate reservoir. Results show that the gas production processes in the two simulators consist of three periods: the free gas production, mixed gas (free gas and gas dissociated from the hydrate) production and gas production from hydrate dissociation. The first and second periods are mainly controlled by the pressure reduction rate. The heat conduction from the ambient is main driving force to dissociate the hydrate in the third period. The cumulative gas production in the third period with the PHS and CHS is much higher than those in the first and second periods. However, the gas production rate in the period is low. The duration for gas production with the PHS is approximately 20 times as many as that with the CHS. Water production behavior with the PHS is different with that with the CHS during the gas production. The system temperature change tendency with the PHS is the same with that with the CHS during the gas production. The unique difference is that there is also a temperature rise period with the CHS. (C) 2012 Elsevier Ltd. All rights reserved.